2021
DOI: 10.1056/nejmoa2032125
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Nivolumab in Resected Esophageal or Gastroesophageal Junction Cancer

Abstract: BACKGROUNDNo adjuvant treatment has been established for patients who remain at high risk for recurrence after neoadjuvant chemoradiotherapy and surgery for esophageal or gastroesophageal junction cancer. METHODSWe conducted CheckMate 577, a global, randomized, double-blind, placebo-controlled phase 3 trial to evaluate a checkpoint inhibitor as adjuvant therapy in patients with esophageal or gastroesophageal junction cancer. Adults with resected (R0) stage II or III esophageal or gastroesophageal junction canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
718
3
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,041 publications
(855 citation statements)
references
References 21 publications
7
718
3
14
Order By: Relevance
“…For locally advanced stages, the five-year survival period is frustrating, ranging from 17-23%, which may be slightly higher in patients with resectable diseases (2)(3)(4)(5), and the current National Comprehensive Cancer Network (NCCN) guidelines recommend neoadjuvant therapy (6). Now, immunotherapy as a new treatment is effective when used alone in resectable esophageal cancer (7). More and more evidence of neoadjuvant immunotherapy suggests that it can improve the prognosis of unresectable tumors, and immunotherapy drugs have become diverse, such as "Camrelizumab, Pembrolizumab or Sintilimab," etc.…”
Section: Introductionmentioning
confidence: 99%
“…For locally advanced stages, the five-year survival period is frustrating, ranging from 17-23%, which may be slightly higher in patients with resectable diseases (2)(3)(4)(5), and the current National Comprehensive Cancer Network (NCCN) guidelines recommend neoadjuvant therapy (6). Now, immunotherapy as a new treatment is effective when used alone in resectable esophageal cancer (7). More and more evidence of neoadjuvant immunotherapy suggests that it can improve the prognosis of unresectable tumors, and immunotherapy drugs have become diverse, such as "Camrelizumab, Pembrolizumab or Sintilimab," etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent randomized trials have demonstrated the value of anti-PD1 and anti-PDL1 in the treatment of advanced or metastatic EC [ 32 , 33 ] and as adjuvant treatment after R0 resection [ 34 ].…”
Section: Multidrug Resistancementioning
confidence: 99%
“…Although this study only included 10 tumour samples, the results are in stark contrast to Western tumour findings and lay the groundwork for further comparative studies between Asian and non-Asian patients. Outcome differences between Asian and non-Asian patients have been conflicting across immunotherapy trials, with CheckMate 649 reporting an overall survival (OS) benefit for Asian patients, whereas no difference was seen for DFS in CheckMate 577 [10,27]. No studies to date have compared the tumour microenvironment (TME) of OAC between Asian and non-Asian patients, and integrative studies comparing the TME and underlying genomic features may inform geographically relevant biomarkers and therapeutic strategies.…”
Section: Genomic Features Of Oac and Associated Immune Responsesmentioning
confidence: 99%
“…Most oesophageal cancer (OC) and gastro-oesophageal cancer (GOC) immunotherapy trials have focussed on second-or third-line treatment of advanced/metastatic disease, and although encouraging, results have only shown modest survival increases compared with CT (Table 1). Recently however, results from the CheckMate-577 trial, where patients treated with adjuvant Nivolumab following CRT and surgical resection, showed significantly increased disease-free survival (DFS) compared to placebo [10] (Table 1).…”
Section: Introductionmentioning
confidence: 99%